BUILDING THE POSITIVE SELF-CONCEPT THROUGH PATRIOTISM - Subaryana, Subaryana (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
Patriotism is self-sacrifice for the nation. This attitude is very important to maintain the existence of the nation and the state. The young generation as a successor generation of the nation absolutely hope to develop patriotism in his life. In this case, the patriotism is patriotism that de-veloped to uphold human values and the constitution and are willing to accept constructive criti-cism. One way to build a constructive is through the establishment of a positive self-concept. This is because of the self-concept is one’s view of himself. The more positive a person sees himself, both of from the physical aspect, psychologies, social, and academic anyway it will be more posi-tive self concept. The self-concept is something important in one’s life, because the self-concept will be able to help a person to identify himself, either from the negative side and a positive side. The self-concept will also give a consideration about what should he do and how one is to behave toward an object. Therefore the self-concept can be a positive control for someone to act and be-have, including patriotism